Oral/Aural: Pastness and Sound as Medium and Method - Erasmus, Aidan; Layne, Valmont (Kronos: Southern African Histories, 2024)
In archival footage uploaded online of a concert at the University of the Western Cape in 1988 musician Robbie Jansen declared that the next composition to be performed was named ‘Freedom Where Have You Been’.1 Before counting the band in, Jansen offered a short discourse on the meaning of the phrase hoya chibongo. Hearing the Afrikaans hoorie (meaning listen here) in the expression hoya, Jansen proceeded to split up the word chibongo to accentuate chi- as aurally reminiscent of the suffix -tjie that is used in Afrikaans to mark the diminutive. bongo, in this context as Jansen remarked, is the drum, leading Jansen to exclaim that the phrase hoya chibongo means to ‘listen to the (small) drum’, the drum that is, according to Jansen, ‘the truth’. In Jansen’s exact words, ‘the drum speaks the truth and the drum has always been our language before these funny words that we are speaking now’.